2013
DOI: 10.1177/2325957412471992
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of the Effects of Depression and Antidepressants on Physical and Work Functioning among Antiretroviral Therapy Clients in Uganda

Abstract: Depression is common among people living with HIV/AIDS in sub-Saharan Africa. Yet, little is known about how depression influences physical health and socioeconomic well-being in the context of antiretroviral therapy (ART). Semi-structured interviews with 40 adult HIV clients receiving ART in Uganda were conducted to assess experiences prior to and after HIV diagnosis and initiation of ART. Content analysis revealed themes that were suggestive of the following patterns: 1) functioning decreased after patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…This finding is consistent with other studies on the general population 5 8,32 and among PLWH. 9,11 Findings support prior studies that relied on clinically diagnosed depression rather than prospective assessment of depression concomitant with physical function among PLWH. 9,33 We found a function score that was on average 10 points lower in patients with depression, adjusted for the effects of age, income, years living with HIV, ART, and comorbidities.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This finding is consistent with other studies on the general population 5 8,32 and among PLWH. 9,11 Findings support prior studies that relied on clinically diagnosed depression rather than prospective assessment of depression concomitant with physical function among PLWH. 9,33 We found a function score that was on average 10 points lower in patients with depression, adjusted for the effects of age, income, years living with HIV, ART, and comorbidities.…”
Section: Discussionsupporting
confidence: 71%
“…34 Although depression can lead to frailty and physical limitations, the reverse direction has also been found. 10,11 Therefore, additional longitudinal research is necessary to understand more fully the bidirectional relationship between depression and physical function. Regardless of causal direction, treating depression at early stages is important, because it can foster physical activity and prevent the development of new or further physical function limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study in Uganda where the diagnosis was made by a psychiatrist reported that 65% of the PLHIV had MDD. Among them, 61.5% were diagnosed after becoming HIV-positive and 38.4% after starting ART [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depression is often considered as a logical outcome in PLHIV and is difficult to diagnose due to its common symptoms with HIV disease such as fatigue, sleeping problems, loss of appetite and cognitive impairment [ 6 , 39 ]. PLHIV report also more easily somatic symptoms than emotional or affective ones [ 38 ]. The lack of time available in primary health care settings, the lack of knowledge of the clinicians on mental health and the poor integration of mental health services in SSA contribute to the difficulties to identify patients with depression [ 80 ].…”
Section: Discussionmentioning
confidence: 99%